EXPLORATION PLAYS IN THE CAUCASUS REGION. (26th June 2021) - Tari, G.; Blackbourn, G.; Boote, D.R.D.; Sachsenhofer, R.F.; Yukler, A.
Abstract : Exploration efforts around the Greater Caucasus region started towards the end of the 19th century and established a wide range of petroleum play types in various basin segments around the orogen. All these plays are associated with the flanks of the inverted thrust‐fold belt and the adjacent foreland basin systems, but display significant variation among the basin segments depending on the tectonostratigraphic units involved and the degree of exploration maturity. Whereas the same main source rocks have generated most of the hydrocarbons in all the basins (namely organic‐rich shales in the Oligocene – Lower Miocene Maykop Group and the Eocene Kuma Formation), it is primarily the trapping style, both proven and speculative, which is responsible for the broad spectrum of play types observed. Eleven play type diagrams across six main petroleum provinces of the Greater Caucasus region are presented in this paper and summarize the current exploration understanding of the existing discoveries and potential new play targets. These play cartoons offer a prospect‐scale summary of both mature producing and underexplored basin segments in a coherent visual manner, and are therefore intended to promote future exploration efforts in the Caucasus region. The testing of new play types requires the proper risking of the two most critical elements in the region: hydrocarbon kitchen effectiveness, and post‐charge trap modification. The de‐risking of these factors will require properly designed, fit‐for‐purpose acquisition of modern geological and geophysical data sets.